Preparation and Spectroscopic Characterization of Iron(III) Complexes of a Functionalized Crown Ether - Raed A. Aubed (مجلة علوم ذي قار, 2019)
This research includes the synthesis and characterization of Shiff's bases crown ethers prepared from condensation between cis-diaminodibenzo-18-crown-6 and benzaldehyde substituted with some groups such as; 4-H , 4-CH2(CH2)6CH 3 , 4-Cl , 4-Br and 4-NO2 and their complexes with Fe(NOO.The study involved solubility, melting points and thermal stability, elemental analysis have been detected with spectral studies using 1 H-NMR, UV-Visible and IR-spectroscopy .Theyfound to be solid crystalline and appear to be salt Shiff's bases crown ethers formed by Iondipole interaction between the cation and the negatively charged oxygen atoms symmetrically placed